2010
DOI: 10.4081/gh.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

Ecological study and risk mapping of visceral leishmaniasis in an endemic area of Iran based on a geographical information systems approach

Abstract: Abstract. Between 1998 and 2001, a total of 1,062 human cases of visceral leishmaniasis were reported from the rural district of Meshkin-Shahr in the mountainous, north-western Iranian province of Ardabil. In the summer of 2008, a cross-sectional study of dogs was conducted in this endemic area by randomly selecting 384 animals from 21 villages and testing them serologically for leishmaniasis. Villages, in which more than 10% of investigated dogs showed antiLeishmania titres ≥1/320, were considered to be high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 8 publications
2
26
1
1
Order By: Relevance
“…nomadic people migrating twice annually. Among other factors, Fu et al (2013) point out the importance of access to healthcare services and lifestyle, while the correlation of VL with rainfall, humidity, elevation, and temperature found here has been confirmed by Salahi-Moghaddam et al (2010).…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…nomadic people migrating twice annually. Among other factors, Fu et al (2013) point out the importance of access to healthcare services and lifestyle, while the correlation of VL with rainfall, humidity, elevation, and temperature found here has been confirmed by Salahi-Moghaddam et al (2010).…”
Section: Resultssupporting
confidence: 62%
“…A number of studies around the world have demonstrated that environmental, demographic and statistical data about the ecology of VL can provide the basis for the development of spatial, predictive risk models (Peterson and Shaw, 2003;Castillo-Riquelme et al, 2008;Salahi-Moghaddam et al, 2010). Geographical information systems (GIS) can be applied for risk mapping and identifying endemic areas for diseases (Elnaiem et al, 2003;Rinaldi et al, 2006;Pezeshki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…No such studies have been conducted in Iran or the neighbouring trans-Caucasus countries, but there is good evidence that the distribution of VL and its vectors in this region depend on environmental variables (Castillo Riquelme et al, 2006;Salahi-Moghaddam et al, 2010). Although multy criteria decision making (MCDM) methods have only been sparsely used for Health-GIS applications based on geographical information systems (GIS), Clements et al (2006) used this approach to obtain a greater understanding of uncertainty related to the geographical distribution of Rift Valley fever (RVF).…”
Section: Introductionmentioning
confidence: 99%